Jesus en die sosiaal-veragtes - Aarde, Andries van (Hervormde teologiese studies, 1988)
Jesus and the social outcasts The article argues that Jesus, as a first century Jew, must be seen as part of the social outcasts of his days. The group, however, should not anachronistically be treated from modem economical and political perspectives. It is illustrated how the social outcasts are led by Jesus to an existence of trust in the presence of God in spite of depressive circumstances and the apparent elusiveness of God.